2014
DOI: 10.3329/seajph.v3i1.17712
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of risk factors for ischemic heart disease in patients attending tertiary care hospitals in India

Abstract: Ischemic heart disease (IHD) is the leading cause of both mortality and forgone healthy years of life among working -age adults (15-69 years) in South Asia. It is the leading cause of death in India and worldwide. For noncommunicable diseases (NCDs), common, modifiable and easily measurable risk factors could be reliably used to predict the future burden of the diseases and to measure the effectiveness of public health interventions. A casecontrol study was undertaken to examine the socio-demographic profile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
6
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 11 publications
6
6
3
4
Order By: Relevance
“…Similar results have been produced by Smith, were a total of 43.7% of patients included in their study (72.3% of cases and 32.8% of controls) were hypertensive [6]. Reference [11] also found that hypertension was present in 62% of cases and 20% in the controls. However, the odds ratios of a hypertensive patient developing CVD that were reported in these studies were lower than those found in this study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similar results have been produced by Smith, were a total of 43.7% of patients included in their study (72.3% of cases and 32.8% of controls) were hypertensive [6]. Reference [11] also found that hypertension was present in 62% of cases and 20% in the controls. However, the odds ratios of a hypertensive patient developing CVD that were reported in these studies were lower than those found in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Likewise, diabetes was prevalent among 29% of the patients (42% within cases and 16% within controls). This is slightly lower than what kapoor et al [11] found (50%). The odds of a diabetic patient developing CVD was 3.725 times (OR 3.725, 95% CI 1.722 -8.057; AOR 6.033, 95% CI 1.630 -22.332) more than a non -diabetic patient.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Kapoor menemukan responden hi pertensi berisiko 6,5 kali untuk menderita pe nyakit jantung koroner. Nababan menyatakan orang yang hipertensi berisiko 2,25 kali untuk menderita penyakit jantung koroner (14) yang tidak memiliki riwayat hipertensi, serta penelitian yang dilakukan oleh Siregar melalui anali sis regresi logistik juga didapatkan hubungan antara penderita hi- pertensi dengan penyakit jantung koroner dengan tingkat kemaknaan p= 0,0005. (15) Pada variabel diabetes melitus ditemukan tidak terlihat adanya hubungan signifikan antara riwayat diabetes melitus terhadap pe nyakt jantung koroner (p-value 0,134).…”
Section: Pembahasanunclassified
“…Kapoor menemukan responden hi pertensi berisiko 6,5 kali untuk menderita pe nyakit jantung koroner. Nababan menyatakan orang yang hipertensi berisiko 2,25 kali untuk menderita penyakit jantung koroner (14) yang tidak memiliki riwayat hipertensi, serta penelitian yang dilakukan oleh Siregar melalui anali sis regresi logistik juga didapatkan hubungan antara penderita hi- …”
Section: Pembahasanunclassified